Multi-Level, Multi-Dimensional Coding for High-Speed and High-Spectral-Efficiency Optical Transmission - Xiang Zhou, Xiang Zhou; Jianjun Yu, Jianjun Yu (Journal of lightwave technology, 2009)
We review and study several single carrier based multi-level and multi-dimensional coding (ML-MDC) technologies recently demonstrated for spectrally-efficient 100-Gb/s transmission. These include 16-ary PDM-QPSK, 64-ary PDM-8PSK, 64-ary PDM-8QAM as well as 256-ary PDM-16 QAM. We show that high-speed QPSK, 8PSK, 8QAM, and 16QAM can all be generated using commercially available optical modulators using only binary electrical drive signals through novel synthesis methods, and that all of these modulation formats can be detected using a universal receiver front-end and digital coherent detection. We show that the constant modulus algorithm (CMA), which is highly effective for blind polarization recovery of PDM-QPSK and PDM-8PSK signals, is much less effective for PDM-8QAM and PDM-16 QAM. We then present a recently proposed, cascaded multi-modulus algorithm for these cases. In addition to the DSP algorithms used for constellation recovery, we also describe a DSP algorithm to improve the performance of a coherent receiver using single-ended photo-detection. The system impact of ASE noise, laser phase noise, narrowband optical filtering and fiber nonlinear effects has been investigated. For high-level modulation formats using full receiver-side digital compensation, it is shown that the requirement on LO phase noise is more stringent than the signal laser. We also show that RZ pulse shaping significantly improves filter- and fiber-nonlinear tolerance. Finally we present three high-spectral-efficiency and high-speed DWDM transmission experiments implementing these ML-MDC technologies.